2015
DOI: 10.1136/bmjopen-2015-008326
|View full text |Cite
|
Sign up to set email alerts
|

What role do pharmacists play in mediating antibiotic use in hospitals? A qualitative study

Abstract: ObjectiveTo understand Australian hospital pharmacists’ accounts of antibiotic use, and the potential role of pharmacy in antibiotic optimisation within a tertiary hospital setting.Design, setting and participantsQualitative study, utilising semistructured interviews with 19 pharmacists in two hospitals in Queensland, Australia in 2014. Data was analysed using the framework approach and supported by NVivo10 qualitative data analysis software.ResultsThe results demonstrate that (1) pharmacists’ attitudes are am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
3
45
1
5
Order By: Relevance
“…The findings of this study strengthen the preceding work indicating the growing role of pharmacists in curbing the injudicious use of antibiotics [15, 16]. Majority of community pharmacists agreed that AMS program is vital for the improvement of patient care.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of this study strengthen the preceding work indicating the growing role of pharmacists in curbing the injudicious use of antibiotics [15, 16]. Majority of community pharmacists agreed that AMS program is vital for the improvement of patient care.…”
Section: Discussionsupporting
confidence: 85%
“…A p<0.001 gave statistical significance. Other studies found similar findings 25,27,36,38 . The International Pharmaceuticals Federation (FIP) and WHO has also recommended prominent roles which pharmacists must play to curb antibiotic resistance.…”
Section: Attitudes Of Pharmacists Towards Antibioticsupporting
confidence: 69%
“…There is literature—largely from the USA,2 but it is still quite limited. A recent study by Broom et al from Australia,3 which used semistructured interviews with 19 pharmacists based in Queensland, regarding pharmacists’ attitudes showed that the profession still has a long way to go in terms of involvement in antimicrobial management. The authors described pharmacists’ attitudes as ambivalent due to three factors.…”
mentioning
confidence: 99%